Estilos de afrontamiento frente a las rupturas amorosas de pareja, en hombres y mujeres con edades entre 18 y 40 años: Investigación sistemática documental (2022)
The objective of the present investigation was to analyze, from systematic hermeneutics, coping styles in the face of love breakups, in men and women aged between 18 and 40 years, for this documentary bibliographic records were obtained as an instrument at the time of collect the information.